1985
DOI: 10.1172/jci112014
|View full text |Cite
|
Sign up to set email alerts
|

Regional alveolar pressure during periodic flow. Dual manifestations of gas inertia.

Abstract: We measured pressure excursions at the airway opening and at the alveoli (PA) as well as measured the regional distribution of PA during forced oscillations of six excised dog lungs while frequency (f12-32 Hzj), tidal volume (VT 15-80 ml]), and mean transpulmonary pressure (PL 125, 10, and 6 cm H20) were varied. PA'S were measured in four alveolar capsules glued to the pleura of different lobes. The apex-to-base ratio of PA'S was used as an index of the distribution of dynamic lung distension. At low ; there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…Unambiguous experimental and numerical evidences of inertial effects have been observed in several studies on flow though branched structures, with special emphasis on the bronchial tree [2][3][4][5][6][7][8][9][10][11][12][13][14]. Such phenomena exists in real lungs but they are more simple to study in a symmetric geometry [15,16].…”
mentioning
confidence: 99%
“…Unambiguous experimental and numerical evidences of inertial effects have been observed in several studies on flow though branched structures, with special emphasis on the bronchial tree [2][3][4][5][6][7][8][9][10][11][12][13][14]. Such phenomena exists in real lungs but they are more simple to study in a symmetric geometry [15,16].…”
mentioning
confidence: 99%
“…At least in theory, HFOV should reduce the potential barotrauma and volutrauma that are commonly associated with more conventional ventilatory modalities and which may be vitally important in the structurally and functionally immature preterm lung. The experimental evidence supporting the generation of small ⌬P A during HFOV was obtained in healthy adult rabbits (1) and excised adult dog lungs (2). Only one study has obtained direct measurements of ⌬P A in both a normal and abnormal lung model (3).…”
mentioning
confidence: 99%
“…In relating differences in phase between Paw and Pes or Ppl to impedance properties of the respiratory system and chest wall, we assumed that flow was uniform through the lung and chest wall so that regional flow remained in phase throughout the thorax. This assumption is at best a rough approximation, as previous studies have shown [1,2,5,6,10,20,23]. Accordingly, a more complex model with multiple pathways within the pulmonary airways to the mediastinum and rib cage is needed to understand fully the effect of a nonuniform chest wall impedance on esophageal and costal pleural pressures during high frequency ventilation.…”
Section: Electrical Analog Modelsmentioning
confidence: 99%
“…Studies in dogs and rabbits during HFV using inductance plethysmography indicated that when the tidal volume approached or exceeded the dead space, the nonhomogeneous mechanical behavior of the chest wall dominated any potential nonhomogeneous mechanical tendency of the lungs [5,6]. By contrast, studies in intact animals [4,25] have found a ventilation distribution similar to that found in excised lungs [1,3]. The preferential ventilation of the caudal lung regions as indicated by alveolar pressure in excised lungs during HFV with large tidal volumes [3] was produced with the use of tracer gas studies [4,25] and parenchymal markers in intact animals [20].…”
Section: Introductionmentioning
confidence: 97%